De laatste confrontatie tussen Rudolph Thorbecke en Gerrit Jan Mulder: de strijd rond Eduard Mulder - Van den Berg, Rob (Studium, 2019)
In 1864 a long-standing political conflict between the liberal leader Rudolph Thorbecke and the royalist, conservative politician and chemistry professor Gerrit Jan Mulder culminated in a battle around the appointment of Mulder’s son Eduard as professor of chemistry in Utrecht. Whereas the political debates between these two giants have stretched out over a much longer period, and have been described earlier, this affair is yet unknown. The explicit personal nature of this sordid affair offers a unique insight into the political mores of the day. Furthermore, it brings to light questions regarding the applicable procedures governing university appointments in general, and more specifically regarding the mandates of the various parties involved: the king, the minister of education and the university.